RISIKO USAHA PENGRAJIN GULA AREN DI KABUPATEN LEBAK, BANTEN KABUPATEN LEBAK, BANTEN - Ratna mega sari; Andjar Astuti; Suherman Suherman; Setiawan Sariyoga; Asih Mulyaningsih (JURNAL AGRIBISNIS TERPADU, 2020)
The purpose of this study is to analyze  risk of palm sugar craftsman business which includes production risk and income risk. The research data used are primary and secondary data which are processed descriptively and quantitatively. Quantitative data is processed using variance analysis, deviation standard and coefficient of variation. The results showed the risk of production of the palm sugar business in Lebak Regency had a high coefficient of variation reaching 0.26086 or 26.09 percent, meaning that every single rupiah produced the risks faced were 0.26086 or 26.09%. the risk received by the brown sugar craftsmen in Lebak Regency is 0.4371 or reaches 43.71% of the income earned by farmers with a deviation standard of 62916.26. craftsmen need to be careful in running a brown sugar business so that the combination of the use of inputs can achieve maximum output and brown sugar businesses achieve efficiency because thus both production risk and revenue risk can be reduced so that the brown sugar business can produce high production and high income